Membentuk Karakter Kepemimpinan Anak Usia 7-9 Tahun melalui Permainan Tradisional - Theresia Avila Clarita Oktavi; Gregorius Ari Nugrahanta (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
Students who disobeyed moral rules, like brawls and corruption, reflected that they did not have leadership character. This study aims to develop a guidebook for traditional games in order to shape the leadership character of children. The research method used was Research and Development (R&D) type ADDIE, namely Analyze, Design, Develop, Implement, and Evaluate. The results of the validation of traditional game manuals had a quality of "Very good" and an average of 3.82 (scale 1-4), with the recommendation "No need for revision". This study used IBM SPSS Statistics version 26 for Windows with a 95% confidence level and a two-tailed test. The Shapiro-Wilk test analysis of the pretest-posttest had normal distribution data. The significance test with paired samples t-test showed the mean score of the posttest (M = 3.6625, SE = 0.06529) was higher than the mean score of the pretest (M = 1.8125, SE = 0.04407) and the value of t(8) = 26.163, p = 0.000 (p < 0.05), meaning Hnull were rejected. The Pearson correlation coefficient (r) of 0.785 was equivalent to 61.70% in the "Large effect" category. The result of the N-gain score analysis was 84.61%, which is included in the "High" criteria. Thus, the traditional game guidebook was effective for shaping and forming the leadership character of children.